Holistic palak cultivation: standardizing media, nutrients in vertical A-frames for extended shelf life efficiency - Prabhadharshini, M. K.; Anand, M.; Amuthaselvi, G.; Irene Vethamoni, P. (Frontiers in Sustainable Food Systems, 2024)
The cultivation of green leafy vegetables is crucial for improving our nation's nutritional security. Challenges like limited arable land and excessive fertilizer use have become significant concerns on cultivating in open field. To address these issues, vertical farming technology, with a focus on space optimization and hydroponic integration to manage fertilizer use, is gaining attention. This experiment aims to determine the best growing media and nutrient solutions for Palak in an A-framed vertical unit. Three growing media were tested: coir pith (M0), Rockwool (M1), and a 1:1 mix of coir pith and vermiculite (M2). Various combinations of water-soluble fertilizers (Ca (NO3)2, MAP, SOP) were used for each crop’s nutrient recipe preparation. Optimal yields were achieved when Palak were grown in a coir pith and vermiculite mix with nutrient concentrations of 60:50:60 ppm. Despite high yields, green leafy vegetables face rapid spoilage and storage challenges. The study examined factors affecting post-harvest quality, including storage conditions (ambient at 35±5°C, refrigerated at 5±5°C), packing substrates (low-density polyethylene, high-density polyethylene covers), and gas compositions with modified atmosphere packaging. Results showed that refrigerated storage with low-density polyethylene packing and a gas composition of 6% O2, 5% CO2, and 89% N2 (G2) resulted in the least deterioration in physiological attributes and overall visual quality. This study highlights the potential of vertical farming technology, precise nutrient management, and advanced post-harvest techniques for sustainable production and preservation of green leafy vegetables to meet our nation's nutritional security needs.